03 KELAYAKAN DAN RISIKO USAHATANI PADI DI DESA TANETE KECAMATAN SIMBANG KABUPATEN MAROS - Jurnal Agribis; Samsinar Samsinar; Mohammad Anwar Sadat; Musawirah Musawirah (Universitas Muslim Maros, 2021)
The objectives of this study are to first determine the amount of production and income of farmers from rice farming. Secondly, knowing the feasibility of rice farming cultivated by farmers. And thirdly, knowing the risk of production and income of rice farming that farmers work for. This research will be carried out in Tanete Village, Simbang District, Maros Regency. To test the first hypothesis about production and income obtained by farmers from rice farming with income analysis, to test the second hypothesis about the feasibility of rice farming in Tanete Village, Simbang District, Maros Regency used quantitative descriptive analysis, and to test the third hypothesis about production risk and farm income risk Rice analysis is used as a risk of production and income can be measured by the magnitude of the variance and standard deviation. Based on the results of research and discussion, it can be concluded that the average production and income earned by farmers is production of 2,344.00 kg and income of Rp. 4,822,383.33. Then the rice farming in Tanete Village, Simbang District, Maros Regency is feasible to be cultivated with a feasibility value of 2.21. And the risk of rice farming production in Tanete Village, Simbang District, Maros Regency is 0.47, while the risk of income is 0.60.